AB0979 Ultrasound-measured radial displacement of the medial meniscus as an indirect sign of mri-detected cartilage damage in patients with medial tibiofemoral osteoarthritis. (12th June 2018) - Georgiev, T.A.; Ivanova, M.; Penkov, M.; Rashkov, R.; Stoilov, R.
Abstract : Background: Extrusion of the medial meniscus is a consequence of the complex interactions among joint structures and altered tissue mechanics involved in the osteoarthritis (OA) process. 1 Potential contributing factors are cartilage loss, meniscal tears, obesity and knee malalignment 2–4 – features strongly associated with knee OA. Ultrasound (US) measurement of medial meniscus radial displacement (MRD) is an easy to implement procedure that may serve as a starting point for assessment of the cartilage loss in patients with knee osteoarthritis. Objectives: The aim of the study was to investigate the correlation between ultrasound-measured MRD and magnetic resonance imaging(MRI)-detected cartilage damage, as a referent method, in patients with medial femorotibial knee OA Methods: 60 osteoarthritic knees of 48 patients (83% female) aged 40 to 80 years, meeting the ACR criteria for knee osteoarthritis, were included in the study. Patients with severe malalignment (varus or valgus deformity ≥20 degrees) were excluded. Radiographic stage was assessed according to the Kellgren-Lawrence (KL) grading system, as only KL I-III knees were included. MRD was measured in millimetres using diagnostic US with patients in the supine (non-weight-bearing) position. Magnetic resonance images were acquired by using 1.5 T MRI and were evaluated by a trained radiologist using Whole-Organ Magnetic Resonance Imaging Score (WORMS) for cartilage abnormalities of the medial femorotibial joint (MFTJ) and medial meniscal tears. Results: There was a significant difference in values of MRD among studied radiographic groups (p<0.001). The mean (SD) levels of MRD were 2.70 (1.43) mm, 3.97 (1.25) mm and 6.03 (1.30) mm for KLI, KLII, and KLIII, respectively. All knees that were KLII/KLIII (n=41) had MRD higher than 1.8 mm (range 1.8–8.7 mm). MRD correlated significantly and positively with WORMS grades for cartilage abnormalities of MFTJ (p<0.001, r=0.758), WORMS grades for medial meniscal tears (p<0.001, r=0.576), and body mass index (BMI) (p=0.011, r=0.315). Correlation between MRD and MRI-detected cartilage damage remained significant after adjustment for age, BMI and medial meniscal tears score. Conclusions: Joint space narrowing (KL >2) on radiography is associated with higher level of meniscal extrusion. Higher values of measured MRD by ultrasound may be indicative of greater cartilage damage of MFTJ. References: [1] Crema, Michel D., et al. "Factors associated with meniscal extrusion in knees with or at risk for osteoarthritis: the Multicenter Osteoarthritis study."Radiology264.2 (2012): 494–503. [2] Hunter, D. J., et al. "The association of meniscal pathologic changes with cartilage loss in symptomatic knee osteoarthritis." Arthritis & Rheumatology54.3 (2006): 795–801. [3] Lerer, D. B., et al. "The role of meniscal root pathology and radial meniscal tear in medial meniscal extrusion."Skeletal radiology33.10 (2004): 569–574. [4] Sharma, Leena, et al. "Relationship of meniscal damage, meniscal extrusion, malalignment, and joint laxity to subsequent cartilage loss in osteoarthritic knees." Arthritis & Rheumatology58.6 (2008): 1716–1726. Disclosure of Interest: None declared